The Entrepreneurial Pattern Sought To Improve Food Security - Zumaeroh Zumaeroh; Agus Prabawa; Siti Muntahanah; Bagus Adhitya; Sodik Dwi Purnomo (Green Publisher Indonesia, 2023)
Agriculture is a sector that has the potential to be developed because it is a buffer for food sovereignty. Therefore it is necessary to change a new paradigm in agricultural development. Agricultural management is not through a farming approach but is business-oriented. The younger generation who are familiar with digital technology is the hope in the regeneration of old farmers. To support the realization of food security, young farmers known as millennial farmers need to be educated about entrepreneurial patterns in agriculture or agripreneurship. The method of community service carried out is counseling which begins with the presentation of the material, continued with discusi, and mentoring is carried out. The target group for community service is millennial farmers in Kroya village who are members of Karang Taruna. The number of participants was 35 people. Counseling is carried out face-to-face. The result of this activity is that young farmers understand that they can develop their business even better, so that this farmer profession can become a decent livelihood for them